Good hygienic-sanitary practices in anthropometric routine in the (post-) COVID-19 pandemic - Silva, Vladimir Schuindt da (2021)
The COVID-19 pandemic has affected several human activities such as anthropometrics measures practices, from the clinical and research fields to the teaching field. Given the lack of effective vaccines and/or drugs against COVID-19, the World Health Organization (WHO) has recommended taking measures to prevent and cope with the disease. These recommendations were subsequently endorsed by the International Society for the Advancement of Kinanthropometry (ISAK), with adaptations to anthropometric routines, which were made to enable comprehensive application in several Anthropometry segments. This point of view aims to emphasize and contribute to security considerations about anthropometric routines in the post-COVID-19 world. It is herein understood that the biosafety protocol presented under this point of view to enable the return and continuation of anthropometric activities, worldwide, regardless of professional training/ qualification/ performance, with respect to life and communities, may also have recurring application to fight other respiratory pathogens with similar potential to turn into pandemics in the future. Demonstrative videos presenting these recommendations, based on this point of view, should be developed to help reinforcing the good hygienic-sanitary practices to be adopted by Anthropometry professionals who carry out human body measurements.